OSMOTIC DEHYDRATION OF CUT APPLE: MASS TRANSFER KINETICS AND MICROSTRUCTURAL CHANGES - Pissarra, J (2019)
Apple cubes were osmotically dehydrated with 40 degrees Bx sucrose and sorbitol solutions. Light microscopy was used to observe the microstructure of fresh and osmotically dehydrated samples. Peleg's model could fit the experimental data and describe the mass transfer kinetics of water loss (WL) and solid gain (SG). The use the sorbitol as osmotic agent. the increase of temperature and concentration of the solution increased the WL during the osmotic dehydration. The average cellular parameters, area and perimeter (size), and circularity, elongation, roundness, and compactness (shape) of fresh samples were 14.281 +/- 6.65x10(3) mu m(2) and 0.486 mm, and 0.73, 1.56, 0.70, 0.83. respectively. The osmotically dehydrated samples presented a decrease in area, circularity, roundness and compactness and an increase in the elongation of the cells, and these changes were higher in samples treated with sorbitol.